Penguatan Pengetahuan Perilaku Personal Hygiene Saat Menstruasi pada Santri Remaja Putri di Pondok Pesantren Al Munawar Jarnauziyyah Kota Tasikmalaya - Sausan Karimah; Mediana Aulia; Risma Najmi Nuradila; Yolanda Priasti Irchamni; Aprilla Andini; Lutfi Hilman Abdullah; Sabila Syahadah Azizah (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2025)
Personal hygiene during menstruation is important to determine the health of reproductive organs in adolescent girls to avoid infection. According to the Central Bureau of Statistics, 2023, the number of adolescent girls in Indonesia in the early adolescent stage is more than 21 million. Errors in maintaining personal hygiene during menstruation can increase the risk of reproductive health disorders in adolescent girls. The purpose of this service is to increase the knowledge and awareness of adolescent girls about the importance of maintaining personal hygiene behavior during menstruation. The method used was an interactive lecture using an educational and participatory approach. The evaluation results showed a significant increase in knowledge scores from an average of 2.65 in the pre-test to 9.30 in the post-test (p<0.001). These results reflect that the lecture method with an educational and participatory approach used, as well as the leaflet media, is effective in increasing the understanding of adolescent female students about the importance of maintaining personal hygiene during menstruation., without any reference or formula.